2016
DOI: 10.1016/j.wace.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparing regional precipitation and temperature extremes in climate model and reanalysis products

Abstract: A growing field of research aims to characterise the contribution of anthropogenic emissions to the likelihood of extreme weather and climate events. These analyses can be sensitive to the shapes of the tails of simulated distributions. If tails are found to be unrealistically short or long, the anthropogenic signal emerges more or less clearly, respectively, from the noise of possible weather. Here we compare the chance of daily land-surface precipitation and near-surface temperature extremes generated by thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…4c). over North America and parts of Asia, which were found to be biased in favour of 288 being overly weak (Angélil et al, 2016). Extremes in all of the current generation HadAM3P-N96, which corresponds to the PRs for hot extremes in Fig.…”
mentioning
confidence: 87%
“…4c). over North America and parts of Asia, which were found to be biased in favour of 288 being overly weak (Angélil et al, 2016). Extremes in all of the current generation HadAM3P-N96, which corresponds to the PRs for hot extremes in Fig.…”
mentioning
confidence: 87%
“…Numerous studies have demonstrated a spatiotemporal-scale dependence of FAR/RR results, in addition to the specific metric being explored (as discussed in Angélil et al, 2016;Cattiaux & Ribes, 2018;Harrington, 2017;Uhe et al, 2016). First, it is well documented that definition of an extreme event is a critical facet of the EEA result.…”
Section: Applications Of Calibrated Languagementioning
confidence: 99%
“…We used Wilcoxon signed-rank tests to test if significantly higher RMSEs were obtained from the downscaled precipitation using ERA-Interim data (Hollander et al, 2015). JRA-55 shares a considerable amount of input data with ERA-Interim (Kobayashi et al, 2015), and exhibits some similarity in the temperature and precipitation data for the study region (Angélil et al, 2016;Dhanya and Villarini, 2017). This similarity may produce a smaller increase in RMSEs than when Rglimclim is transferred from JRA-55 to a generic climate model.…”
Section: Rglimclimmentioning
confidence: 99%